Analisis Rasio Likuiditas, Aktifitas, Solvabilitas dan Profitabilitas Pada Sektor Poultry yang Terdaftar di ISSI (2018-2022) - Yahya Aditya Rahman; Siti Fajriati Hayati Nafi'ah; Hayati Nafi'ah; Adelina Citra Dewi (Jaksya: Jurnal Akuntansi Syariah, 2023)
This study aims to determine the financial analysis of companies in the Poultry industrial sector which are listed on the Syari'ah Stock Index 2018-2022, with the measuring instrument used is financial ratio analysis consisting of liquidity ratios, solvency ratios, activity ratios and profitability ratios. The research objects used in this study were four publicly traded companies engaged in livestock, namely PT Charoen Pokphand Tbk, PT Japfa Comfeed Tbk, PT Malindo Feedmill Tbk and PT Sreeya Sewu Indonesia. Based on the results of ratio analysis in the Liquidity Ratio, there are two companies that are above the industry average and two companies that are still below the industry average. From the solvency analysis, there is one company that is said to be good which is below the industry average and three companies that are not good because it is above the industry average. From the activity analysis, there are two companies that are above the industry average and two companies that are still below the industry average. From the Average Profitability analysis, there are two companies that are above the average and two companies that are still below the industry average